2021
DOI: 10.1186/s12876-021-01606-x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline thrombopoietin level is associated with platelet count improvement in thrombocytopenic chronic hepatitis C patients after successful direct-acting antiviral agent therapy

Abstract: Background Thrombocytopenia can rapidly improve in chronic hepatitis C (CHC) patients receiving direct-acting antiviral agents (DAA). The role of baseline (BL) thrombopoietin (TPO) in this phenomenon is unclear. Methods From June 2016 to February 2019, a total of 104 CHC patients receiving DAA, with a sustained virologic response and BL thrombocytopenia, at Dalin Tzu Chi Hospital, were enrolled in this retrospective study. Significant platelet coun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Some of these studies did not investigate the predictive factors of significant platelet count improvement. Besides, our previous studies only showed that the fatty liver, baseline platelet counts, and baseline thrombopoietin level were related to significant platelet count improvement [13,15]. In this larger-scale study, we found that age, baseline platelet counts, baseline total bilirubin levels, and cirrhosis were negatively correlated, but the presence of DM was positively correlated with significant platelet count improvement (Table 2).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Some of these studies did not investigate the predictive factors of significant platelet count improvement. Besides, our previous studies only showed that the fatty liver, baseline platelet counts, and baseline thrombopoietin level were related to significant platelet count improvement [13,15]. In this larger-scale study, we found that age, baseline platelet counts, baseline total bilirubin levels, and cirrhosis were negatively correlated, but the presence of DM was positively correlated with significant platelet count improvement (Table 2).…”
Section: Discussionmentioning
confidence: 60%
“…Platelet counts can improve immediately after DAA treatment in CHC patients [11][12][13][14][15]. Some of these studies did not investigate the predictive factors of significant platelet count improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrombocytopenia is a common complication in chronic HCV infection, causing an increased risk of bleeding[ 94 , 95 ]. The prevalence and severity of thrombocytopenia increase with the progression of liver disease and the development of hepatocellular damage and hepatic fibrosis[ 96 ].…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%